Research on the Management of Student Entrepreneurship Development in Higher Education - Lai, Wenya; Chang, Yuancheng; Wang, Xinhai (Journal of Higher Education Theory and Practice, 2023)
Entrepreneurial opportunity identification has attracted much attention in the field of entrepreneurial development as an important factor in the future success of university students in entrepreneurship. Based on experiential learning theory, this study proposes a moderated mediation model to investigate the relationship between entrepreneurial learning (EL) and entrepreneurial opportunity identification, the mediating role of entrepreneurial alertness (EA) and the moderating role of the entrepreneurial environment (EE). A snowball sampling method was used to collect 1263 questionnaires, of which 1164 were valid. The findings revealed that (1) entrepreneurial learning has a positive and significant effect on entrepreneurial opportunity identification among university students; (2) entrepreneurial alertness plays a partially mediating role between entrepreneurial learning and entrepreneurial opportunity identification; (3) entrepreneurial environment plays a moderating role between entrepreneurial learning and entrepreneurial opportunity identification, Compared with a low-level entrepreneurial environment, a high-level entrepreneurial environment can promote the impact.